PENGARUH KESADARAN MEMBAYAR PAJAK DAN PENGETAHUAN TENTANG PERATURAN PERPAJAKAN TERHADAP KEMAUAN MEMBAYAR PAJAK (Studi Kasus Wajib Pajak Orang Pribadi Di KPP Pratama Banjarmasin) - Rusmanto -; Indra Saputra; Retno Suci Lestari (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2018)
Abstract, This research aims to provide empirical evidence about the effect of awareness of paying taxes and knowledge of tax regulations on the willingness to pay taxes (case study of individual taxpayers at KPP Pratama Banjarmasin). The population in this study Individual Taxpayers in the city of Banjarmasin amounted to 180,757. The sampling method used in this study is insidential sampling with the formula of Slovin formula totaling 400 samples. The results showed that awareness of paying taxes does not influence the willingness to pay taxes partially, the knowledge of taxation regulations has a partial effect on the willingness to pay taxes, and awareness of paying taxes and knowledge of tax regulations have simultaneous or simultaneous influence on the variable willingness to pay taxes.